Effect of dual NEPCM and tapered fins on thermal runaway control in lithium-ion batteries - S. Shivram; R. Harish (Case Studies in Thermal Engineering, 2024)
This research investigates the thermal performance of dual phase change materials (PCMs) RT82 (PCM1) and RT27 (PCM2) using tapered fins and nanoparticles to improve their thermal management capabilities, specifically for controlling excessive heating in lithium-ion battery cells. The primary objective is to enhance heat transfer efficiency and melting characteristics of dual PCMs by incorporating alumina (Al2O3), molybdenum disulfide (MoS2), and single-walled carbon nanotubes (SWCNTs) nanoparticles at varying volume fractions and configuring tapered fins in different arrangements. A series of parametric studies were conducted to analyze the impact of these modifications on the thermal transport and solid-liquid transition characteristics of the PCMs. The key findings indicate that the incorporation of nano-sized particles significantly enhances the thermal conductivity of PCMs, with SWCNTs showing the highest improvement. The PCM system with 6 % SWCNTs nanoparticles exhibited a 41.85 % increase in melting characteristics compared to the baseline PCM. The study also reveals that increasing the number of fins from two to eight results in a 94.28 % increase in the melting rate for RT82 and a 50 % increase for RT27. Furthermore, the combination of increased nanoparticle concentration and fin number leads to a 12.17 % rise in melt pool temperature distribution for 2 % SWCNTs and 14.08 % for 6 % SWCNTs. The enhanced thermal conductivity and efficient heat transfer due to the synergistic effect of fins and nanoparticles result in faster phase transitions and improved temperature regulation within the system. These findings underscore the potential of optimized PCM configurations with advanced materials for superior thermal management solutions in high-heat applications, effectively extending the operational efficiency and lifespan of thermal systems like lithium-ion batteries.